Co-circulation and genomic recombination of coxsackievirus A16 and enterovirus 71 during a large outbreak of hand, foot, and mouth disease in Central China. - Weiyong Liu; Shimin Wu; Ying Xiong; Tongya Li; Zhou Wen; Mingzhe Yan; Kai Qin; Yingle Liu; Jianguo Wu (PLoS ONE)
A total of 1844 patients with hand, foot, and mouth disease (HFMD), most of them were children of age 1-3-year-old, in Central China were hospitalized from 2011 to 2012. Among them, 422 were infected with coxsackievirus A16 (CVA16), 334 were infected with enterovirus 71 (EV71), 38 were co-infected with EV71 and CVA16, and 35 were infected with other enteroviruses. Molecular epidemiology analysis revealed that EV71 and CVA16 were detected year-round, but EV71 circulated mainly in July and CVA16 circulated predominantly in November, and incidence of HFMD was reduced in January and February and increased in March. Clinical data showed that hyperglycemia and neurologic complications were significantly higher in EV71-infected patients, while upper respiratory tract infection and C-reactive protein were significantly higher in CVA16-associated patients. 124 EV71 and 80 CVA16 strains were isolated, among them 56 and 68 EV71 strains were C4a and C4b, while 25 and 55 CVA16 strains were B1a and B1b, respectively. Similarity plots and bootscan analyses based on entire genomic sequences revealed that the three C4a sub-genotype EV71 strains were recombinant with C4b sub-genotype EV71 in 2B-2C region, and the three CVA16 strains were recombinant with EV71 in 2A-2B region. Thus, CVA16 and EV71 were the major causative agents in a large HFMD outbreak in Central China. HFMD incidence was high for children among household contact and was detected year-round, but outbreak was seasonal dependent. CVA16 B1b and EV71 C4b reemerged and caused a large epidemic in China after a quiet period of many years. Moreover, EV71 and CVA16 were co-circulated during the outbreak, which may have contributed to the genomic recombination between the pathogens. It should gain more attention as there may be an upward trend in co-circulation of the two pathogens globally and the new role recombination plays in the emergence of new enterovirus variants.